Physiological Profile, Metabolic Response and Temporal Structure in Elite Individual Table Tennis: Differences According to Gender - Francisco Pradas (MDPI AG, 2021)
No research that has analyzed the structural characteristics, physiological profile, and energy demands in the game of table tennis as played by women is available. The present study aimed to evaluate the physiological, metabolic, and temporal variables of table tennis players and to observe gender differences. Forty-eight elite table tennis players participated in this study: 24 men (25.3 ± 4.07 years) and 24 women (22.3 ± 3.8 years). During simulated competition, temporal structure, heart rate (HR), and lactate (LA) were evaluated. The maximum ergospirometric evaluations were performed in a laboratory. The total table tennis (TT) time and the total resting time (TRT) were longer for men (p < 0.05), but game density was higher for women (p < 0.05). During rallies, the real playing time (RPT) was longer for women, while the TRT was longer for men (p < 0.05). The maximum HR, minimum HR, and maximum LA concentrations were higher for men (p < 0.05). The obtained data reveal gender differences in the physiological, metabolic, structural, and temporal variables in table tennis players. The analysis of the studied variables could allow training sessions to be planned and organized according to table tennis players’ gender.